Characterization of Groundwater Quality in the Transitional Plain of Luni Basin and its Suitability for Agricultural Uses - Panwar, N.R.; Kumar, Shrvan; Kumar, Mahesh; Kumar, Praveen; Roy, S; Pandey, C.B. (Annals of Arid Zone, 2023)
Groundwater quality was assessed for irrigation purposes by collectinggroundwater samples from 113 locations during pre-monsoon seasons in Jalore district(Rajasthan). These groundwater samples were analyzed for physico-chemical parameterslike pH, EC, TDS, major cations, and anions. Furthermore, irrigation quality indices likesalinity hazard, chloride hazard, carbonate and bicarbonate hazard and sodium hazardwere calculated using the analytical results. These parameters were compared withstandard limits for irrigation use for the prevailing crops. Generally, hydrochemicalresults indicate that the groundwater in the study area is neutral to very stronglyalkaline in nature. Based on the EC classification, most of the groundwater samples arefalling under the high to very high salinity hazard category. The order of abundanceof major cations and anions in groundwater was found as Na+>Ca2++Mg2+>K+ andCl–>SO42–>HCO3–>CO3–. Based on the EC and SAR, classification >60% of the samples isfalling under the moderate to a high reduction in infiltration rate category. In addition,the study also emphasized that the practice of very high saline and moderately sodicgroundwater for irrigation may cause soil salinity as well as sodicity in soils. The studyfound that the majority of the groundwater samples are above the minimum irrigationwater quality standards, suggesting that necessary action is required for sustainablecrop production by using appropriate management practices in the area.